Analisis Faktor-Faktor yang Mempengaruhi Kinerja Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2015-2018 - Irwan Abdi Nugroho; Kartika Hendra Ts; Suhendro Suhendro (Universitas Batanghari Jambi, 2021)
This study aims to determine, test and analyze Liquidity, Capital Adequacy, Firm Size, Good Corporate Governance and Profitability of banking companies in Indonesia that are listed on the Indonesia Stock Exchange (BEI), the quarterly financial reports of 29 banking companies for the 2015-2018 period. This research is a quantitative research. The population in this study are banking companies listed on the Indonesia Stock Exchange (BEI). The sample in this study was taken using a purposive sampling method that met the sample criteria desired by the researcher. The data used in this study were in the form of documentation. The data analysis technique used in this research is multiple linear regression analysis and classical assumption test. Based on these results, what is done shows that Liquidity, Capital Adequacy, Firm Size and Good Corporate Governance affect the profitability of banking companies.